DNA‐Based Nanoarchitectures as Eminent Vehicles for Smart Drug Delivery Systems. (3rd March 2022) - Komiyama, Makoto; Shigi, Narumi; Ariga, Katsuhiko
Abstract: In order to cure diseases efficiently with minimal side effects in sophisticated medicine, eminent drugs must be selectively delivered to diseased parts and allow to work only there. However, most of drug delivery systems (DDSs) previously proposed are not yet sufficiently selective and effective. This review covers recent developments of DDS in which DNA nanoarchitectures are employed as drug carriers. From short DNA fragments, a variety of complicated nanomedicines are fabricated to show unprecedentedly smart DDS functions. Encapsulated drugs are released mostly through controlled disassembly of DNA nanoarchitectures. Recent attention has been focusing to the use of appropriate stimuli to regulate each process in the DDS (delivery of drug, its release, and others) for further improved therapy. As intracellular stimuli for the regulation, various endogenous compounds (e.g., mRNA and enzymes), which are specifically abundant in target cells, are employed. Alternatively, physical perturbation (e.g., light irradiation) is provided from outside of tissues to control DDS. By combining multiple strategies in terms of new concepts, enormously smart DDSs are being achieved. Further progresses of these approaches in the future are guaranteed by complete freedom of molecular design in DNA nanoarchitectonics. Abstract : This review covers recent developments of drug delivery system (DDS) with various DNA nanoarchitectures nanoparticles, and others). Furthermore nanoarchitectonics for DDSs driven by intracellular factors (mRNA, enzymes, and others) and external stimuli (e.g., light) are discussed. With these progresses, new DDS modes can be envisioned to make predominant contributions to pharmaceutics, medicine, and many other related fields.